Adapting a complex health intervention guided by the core functions and forms model: a methodology and case example of participatory adaptation - Kirsten E. Austad; Nhi Nguyen; Elizabeth Jadovich; Bridget Poznanski; Max Laguerre; Alicia Fernandez; Mari-Lynn Drainoni; Brian Jack; Suzanne Mitchell; Ramzi G. Salloum; Graham Moore (Frontiers in Health Services, 2026)
Intervention adaptation—the intentional modification of a program, practice, or innovation's design or delivery—is essential for improving fit when interventions are implemented with diverse populations, yet how to adapt without compromising core mechanisms remains a persistent challenge for complex, multicomponent programs. This article describes how the Core Functions and Forms (CFF) model, used in conjunction with the ADAPT guidance, addresses this challenge by distinguishing essential intervention mechanisms (core functions) from adaptable delivery strategies (forms). To illustrate the approach, we present a case example of adapting hospital discharge interventions for patients with non-English language preference. A 13-member Adaptation Team of patients, caregivers, and hospital staff participated in four facilitated sessions to identify and prioritize core functions shared across existing discharge interventions, then propose context-appropriate forms—distinguishing specific forms tied to individual functions from cross-cutting forms spanning who delivers the intervention, when, where, and how language concordance is achieved. Rankings and impact–feasibility ratings informed deliberative prioritization, surfacing functions that balanced high impact with feasibility as well as those judged impactful but harder to implement. Applying the CFF model across a family of related interventions, rather than a single program, shows how shared mechanisms can be reused and tailored for diverse populations. This manuscript reports the adaptation-design phase; subsequent pilot testing is planned. The approach offers a transparent, replicable method for equity-focused adaptation that preserves intervention mechanisms while tailoring delivery.